PARENTING MANAGEMENT OF PARENTS IN IMPROVING ABILITY TO READ THE QURAN IN EARLY CHILDREN - Royani Harahap, Nikmah; Irwansyah, Irwansyah; Sari Harahap, Hotni; Handayani, Afnita (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to describe the role of parenting style, the relationship between parenting style and the success factors of parenting style in learning the Qur'an for early childhood. This study used a qualitative method with data collection techniques in the form of interviews, observations and documentation, as well as triangulation and data analysis. The results of the study show that the role of parents is very large in the obligation to care for and maintain the survival of their children, as well as meeting the basic needs of children, both physical-biomedical (asuh), emotional/love needs (love), and the need for mental stimulation. Therefore, parenting style is very strongly related to the achievement of children's Al-Qur'an learning. however, the implementation of parenting itself is inseparable from the factors that influence it, namely the personality of parents, similar parenting patterns, religion, environment, education, gender, social status, child's ability, and situation. This research is expected to contribute to parents in determining parenting according to the situation and condition of the child.